UPAYA OPTIMALISASI PRODUKSI ASI MELALUI PENYULUHAN POLA MAKAN IBU MENYUSUI - Cut Oktaviyana; Syarifah Masthura; Dewi Sartika; Fauziah Fauziah (Universitas Ubudiyah Indonesia, 2025)
The inability to produce an adequate supply of breast milk is frequently the primary factor leading to the premature cessation of exclusive breastfeeding. A lack of maternal understanding regarding healthy dietary patterns and the consumption of galactagogues (lactation-enhancing foods) poses a significant risk. Health education serves as a cognitive approach to improve maternal knowledge of nutrition during the lactation period. This study aims to enhance the knowledge of breastfeeding mothers concerning dietary habits as an effort to optimize breast milk production. This research employed a quantitative method with a pre-experimental